Kajian Fikih Ibadah Tentang Tayamum, Perawatan Jenazah, dan Manasik Haji - Wulandari Berliana Sapyudin; Destri Azahra; Kurnia Ahmad Susilo; Naila Rahma Aulia; Zahrotul Mukarromah; Nur Wakhid (Jurnal Ilmiah Literasi Indonesia, 2026)
The lack of public understanding regarding tayamum, funeral management, and hajj rituals in accordance with islamic teachings still often leads to mistakes in their implementation. This study aims to understand the concepts, procedures, and applications of tayamum, funeral management, and hajj rituals in daily life. The method used in this study is qualitative research with a library research approach through collecting data from books, scientific journals, and various relevant literature sources. The collected data were then analyzed descriptively. The results of the study indicate that public understanding of these three aspects of fiqh worship still needs to be improved. The low level of public understanding is influenced by limited education, restricted learning resources, and the lack of direct practical experience. Therefore, a more practical and easily understood fiqh learning approach is needed so that the implementation of worship can be carried out properly in accordance with islamic law